Aspek Reproduksi Ikan Toman (Channa micropeltes Cuvier) Di Danau Kelubi Kecamatan Tayan Hilir Kabupaten Sanggau - Tri Rima Setyawati, Nor Aeni Sonnaria, Ari Hepi Yanti, (Universitas Tanjungpura, 2015)
Snakehead fish (Channa micropeltes Cuvier) is economical freshwater fish which are found in Kelubi Lake. Over time, Kelubi lake had changed by activity around the lake and impact on biota in it. The purpose of this research to gain information about aspects of snakehead fish reproduction in the Kelubi Lake which involve include density, sex ratio, level of gonad maturity, index of gonad maturity, fecundity, and egg diameter, along with aspects of marine environment Kelubi Lake. This research have been done at December, 2013 untill February, 2014. Sampling technique using Proportionate Cluster Random Sampling with fishnet stocking area 12,56 m2. Based on Catch per Unit Effort (CPUE) analyst is known snakehead fish density in Kelubi Lake is 439 fishes. Sex ratio between snakehead fish male and female is 2:1. Population is dominated by widhitebait with level of gonad maturity (TKG) I. Index of gonad maturity is about 0,03-0,94%,indicates that snakehead fish can spawn year-around. Snakehead fish fecundity as about 14.056 grains/fish and egg diameter range between 2,30-2,57 mm.